2016
DOI: 10.20510/ukjpb/4/i4/112413
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Childhood Asthma in Fayoum City (District) Egypt

Abstract: Asthma is a major public health problem worldwide. There was a sharp increase in the global prevalence of asthma over the last two decades. Few studies evaluated asthma prevalence in Egypt. Determination of the prevalence of bronchial asthma among school children aged 6-12 years old in Fayoum city (distrect) and identification of the risk factors associated with asthma. A questionnaire-based study conducted in the period from Feb to April 2013. We used a modified written International Study of Asthma and Aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In Egypt, Bronchial asthma was prevalent among schoolchildren in El-Fayoum city [district] at 6.3% [20] . Most of the pitfalls of asthma treatment are under diagnosis and under treatment in childhood asthma.…”
Section: Asthma and Socio-demographic Charactersmentioning
confidence: 99%
“…In Egypt, Bronchial asthma was prevalent among schoolchildren in El-Fayoum city [district] at 6.3% [20] . Most of the pitfalls of asthma treatment are under diagnosis and under treatment in childhood asthma.…”
Section: Asthma and Socio-demographic Charactersmentioning
confidence: 99%
“…It mainly occurs in young children and has an 8%–28% incidence and prevalence globally, and it is increasing yearly 4 . In Egypt, the prevalence of asthma among school children in the Nile Delta region is about 7.7% 5 with probably underdiagnosis and undertreatment, particularly among children from less wealthy families 6 . Other studies reported an incidence of 9.4% in 11–15‐year‐old adolescents 7 .…”
Section: Introduction and Scopementioning
confidence: 99%